Optimization of a glass fiber membrane based column for improved in-house pcr DNA purification - Zaidi, Muhammad Hafiz (Universiti Sains Malaysia, 2025)
Column-based PCR purification is commonly used in laboratories to purify PCR amplicons for various downstream applications including sequencing and cloning. The commercially available products such as the Qiagen PCR DNA purification kit, which comes with GMP are designed intended for research usage. For manpower training or academic education, a less expensive kit with comparable performance could be a better option. An in-house self-assembled PCR purification kit using a glass fiber membrane was developed in the present study, while the QIAGEN kit was used as the reference kit. For optimization, columns with different membrane pore sizes (0.22 μm, 0.45 μm, and 0.80 μm) and membrane layers (1, 2, and 6) were assembled and tested. The yield and DNA purities were analyzed via bio-photometer and compared. For results, columns utilizing GF membrane of a smaller pore size i.e. 0.22 um showed the highest DNA yield. DNA membrane with 6 layers also retains the highest DNA yield. In the comparative study, GF based column showed higher performance than the in-house silica membrane and a comparable DNA yield to the QIAGEN kits. All kits showed good DNA purities for A260/A280 purities, but not for A260/A230 purities. Nonetheless, the DNA bands showed to be good in agarose gel DNA electrophoresis analysis. This study suggests that optimized in-house glass fiber membranes offer a viable and affordable alternative for PCR DNA purification, bridging the cost-efficiency gap for resource-limited laboratories